Ultraviolet Filters: Dissecting Current Facts and Myths - Breakell, Thomas; Kowalski, Isabel; Foerster, Yannick; Kramer, Rafaela; Erdmann, Michael; Berking, Carola; Heppt, Markus (Journal of Clinical Medicine, 2024)
Skin cancer is a global and increasingly prevalent issue, causing significant individual and economic damage. UV filters in sunscreens play a major role in mitigating the risks that solar ultraviolet ra-diation poses to the human organism. While empirically effective, multiple adverse effects of these compounds are discussed in the media and in scientific research. UV filters are blamed for the dis-ruption of endocrine processes and vitamin D synthesis, damaging effects on the environment, induction of acne and neurotoxic and carcinogenic effects. Some of these allegations are based on scientific facts while others are simply arbitrary. This is especially dangerous considering the risks of exposing unprotected skin to the sun. In summary, UV filters approved by the respective governing bodies are safe for human use and their proven skin cancer-preventing properties make them in-dispensable for sensible sun protection habits. Nonetheless, compounds like octocrylene and ben-zophenone-3 that are linked to the harming of marine ecosystems could be omitted from skin care regimens in favor of the myriad of non-toxic UV filters.
CRIS-Team Scopus Importer:2024-06-14
Keywords: benzophenones; carcinogen; endocrine disruption; marine environment; octocrylene; prevention; skin cancer; sunscreen; UV filters; vitamin D